Opportunities and Challenges: Professional Development Programming in Media and Communication Education. (December 2020) - Crawford, Jerry; Boyles, Jan Lauren; Hernandez, Terri; Lou, Chen; Cheng, Hong; Perlmutter, David
The Association for Education in Journalism and Mass Communication (AEJMC) leadership charged a 13-member Presidential Task Force on Careers to obtain membership's thoughts on preferences and needs regarding career-assistance programming and activities. This Spring 2019 report details a survey of the interest of educators, of all ranks, in current AEJMC efforts and the need for more targeted and accessible opportunities, both at annual conferences and online modules. Results included members' thoughts on professional development, burnout, tenure and posttenure processes, academic culture, and the importance of being forward thinking regarding news and strategic communications industries outside of academia.